2019
DOI: 10.3390/jcm8091400
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Role of Secreted Engrailed Homeobox 2 (EN2) in Prostate Cancer

Abstract: Engrailed variant-2 (EN2) has been suggested as a potential diagnostic biomarker; however, its presence and functional role in prostate cancer (PCa) cells is still controversial or unknown. Here, we analyzed 1) the expression/secretion profile of EN2 in five independent samples cohorts from PCa patients and controls (prostate tissues and/or urine) to determine its utility as a PCa biomarker; and 2) the functional role of EN2 in normal (RWPE1) and tumor (LNCaP/22Rv1/PC3) prostate cells to explore its potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Cell lines derived from normal prostate (RWPE-1) and from androgen-dependent (LNCaP), sensitive (22Rv1) and non-dependent (PC-3) PCa were obtained from the American Type Culture Collection (Manassas, VA, USA) and cultured in a humidified incubator with 5% CO 2 at 37 • C according to manufacturer instructions, as previously described [32][33][34]. An analysis of short tandem repeat sequences (STRs) was performed to validate these cell lines by using GenePrint 10 System (Promega, Barcelona, Spain), and the absence of mycoplasma was confirmed by PCR as previously reported [35].…”
Section: Cell Culturementioning
confidence: 99%
“…Cell lines derived from normal prostate (RWPE-1) and from androgen-dependent (LNCaP), sensitive (22Rv1) and non-dependent (PC-3) PCa were obtained from the American Type Culture Collection (Manassas, VA, USA) and cultured in a humidified incubator with 5% CO 2 at 37 • C according to manufacturer instructions, as previously described [32][33][34]. An analysis of short tandem repeat sequences (STRs) was performed to validate these cell lines by using GenePrint 10 System (Promega, Barcelona, Spain), and the absence of mycoplasma was confirmed by PCR as previously reported [35].…”
Section: Cell Culturementioning
confidence: 99%
“…Therefore, more novel biomarkers are urgently needed to detect UCB in general and especially in high-risk populations where the disease prevalence appears to be high (12,13). The transcription factor Engrailed-2 (EN2) was previously shown to be a specific and potentially sensitive marker for bladder and prostate cancer (14)(15)(16)(17)(18)(19)(20). Using a standard ELISA method, we have previously shown that urinary EN2 could be detected and used as a UCB diagnosis biomarker, even in the early and non-invasive stages of the disease (15).…”
Section: Introductionmentioning
confidence: 99%